# Mathematical expressions using short multiplication formulas

### Mathematical expressions using short multiplication formulas

Solve these mathematical expressions using short multiplication formulas:

(2x-3)(2x+3)-(x-3)(x+3)= ?

x(x+3)(x-3)-(x+1)(x+2)(x-1)= ?
sisoni

### Re: Mathematical expressions using short multiplication form

About the both expressions use this short multiplication formula: $$(a - b)(a + b) = (a^2 - b^2)$$
$$(2x-3)(2x+3)-(x-3)(x+3) = ((2x)^2 - 3^2) - (x^2 - 3^2) = 4x^2 - 9 - x^2 + 9 = 3x^2$$

Math Tutor

Posts: 410
Joined: Sun Oct 09, 2005 11:37 am
Reputation: 28

### Re: Mathematical expressions using short multiplication form

x(x+3)(x-3)-(x+1)(x+2)(x-1)= x((x+3)(x-3)) - ((x+1)(x-1))(x+2) =
=x(x^2 - 9) - (x^2 - 1)(x+2) = x^3 - 9x - (x^3 + 2x^2 - x - 2) = x^3 - 9x - x^3 - 2x^2 + x + 2 = -2x^2- 8x + 2

John

### Re: Mathematical expressions using short multiplication form

The formulas is (a+b)(a-b) = a^2 - b^2
So you cans solve this answer of Rational Expressions in mathematical world. But be prepare to solve yourself .Thanks.         Guest